A comprehensive review of Asherman's syndrome: causes, symptoms and treatment options. Issue 4 (August 2017) - Salazar, Christina A.; Isaacson, Keith; Morris, Stephanie
Abstract : Purpose of review: Intrauterine adhesions, also known as Asherman's syndrome, can have an impact on both reproductive outcomes and gynaecologic symptoms. Understanding the cause of intrauterine adhesions and the common clinical presentation will increase awareness of the condition and guide the patient to appropriate therapy. Surgical management offers favourable fertility outcomes and is often successful in restoring menstruation. Recent findings: Surgical management with hysteroscopic lysis of adhesions is the gold standard for treatment and adopting an office-based approach offers several advantages. Prevention of reformation of adhesions remains challenging and no single method for preventing recurrence has shown superiority. Cell-based therapies using endometrial stem/progenitor cells hold promise for future use in regenerating inadequate endometrium. Summary: Increased awareness of the symptoms suggestive of intrauterine adhesive disease, as well as recognition of common causes and preceding events, is crucial for early diagnosis, patient counselling and treatment. Video abstract: http://links.lww.com/COOG/A36 . Abstract : Supplemental Digital Content is available in the text